Modulation of fruit ripening, storage time and quality of fruits with emulsion of Chitosan alone and loaded with Salicylic acid or Oxalic acid - Azzu, Youssef Mohamed (Curtin University, 2016)
Efficacy of chitosan emulsion, salicylic acid (SA) or oxalic acid (OA) alone and chitosan loaded with SA or OA on ethylene production, extending storage life and maintenance of climacteric (nectarine and plum) and non-climacteric fruit (sweet orange) quality at ambient temperature and cold conditions was investigated. Beneficial effects of these coating treatments in regulating ethylene production, fruit softening, reducing weight loss and diseases and quality parameters varied between climacteric and non-climacteric fruits, cultivars and storage conditions.